Technologies For Preparing Future Teachers For Innovative Activity Based On A Competent Approach - Gulhayo Khasanova (Euro Asian Journal Publishing, 2024)
Through this article, it will be discussed about the future teachers' competence and how to choose teaching methods in practice. Improving the effectiveness of the professional potential of future educators with the help of innovative technologies, preparing them for innovative activities at the level of the requirements of the time, and the status of its implementation in educational activities, increasing the effectiveness of their professional potential by developing the intellectual ability of educators, and the role and advantages of developing them with the help of innovative technologies are highlighted
Keywords: innovation; competence approach of future educators